A retrospective analysis of acupuncture practice in dogs in selected veterinary clinics in Klang Valley - Goh, Joy Xine (2018)
Acupuncture has been widely used as an adjunct to conventional western veterinary medicine. Due to lacking of data on veterinary acupuncture in dogs in Malaysia, a retrospective study was carried out to document the distribution of acupuncture cases, acupuncture methods used, concurrent treatments with acupuncture, subjective outcomes and side effects in dogs treated with acupuncture. Medical records of dogs underwent acupuncture therapy at two selected veterinary clinics with the certified acupuncturists in Klang Valley from January to December 2017 were reviewed. Data on signalments, common presenting signs, concurrent treatments, treatment outcomes, and side effects of acupuncture were retrieved and were summarised as descriptive statistics. A total of 194 acupuncture cases in dogs had been recorded. Patients presented were mainly composed of the geriatric group (71%). Small breed dogs made up 49% of the overall acupuncture cases. The most common chief complaints presented were neurological problems (40.9%) followed by orthopaedic problems (27.4%), with intervertebral disc disease (IVDD) (56.3%) and arthritis (46.3%) being the predominant issues respectively. In summary, this study visualized the use of veterinary acupuncture in dogs in Klang Valley and the information will be useful for designing efficacy study in the future.